APPLICATION OF THE DEVELOPMENT VILLAGE INDEX (IDM) APPLICATION TO BULANG VILLAGE INFRASTRUCTURE - Maulidia Hapsari; Hendra Sukmana (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the impact of the implementation of the Building Village Index (IDM) Application on infrastructure development in Bulang Village, Prambon District, Sidoarjo Regency. The main focus is on how these systems affect the effectiveness and efficiency of planning and implementing data-driven development. Method: The research uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The informants consisted of village officials, IDM operators, and village development experts. Data analysis was carried out using the Miles and Huberman model which includes reduction, presentation, and drawing conclusions. Results: Based on the theory of information system application by Indrajit (2006), the success of the implementation of the IDM application is analyzed through four main indicators: (1) the readiness of the technological infrastructure, which is still experiencing obstacles in network and server stability; (2) human resource capabilities, where village officials show high adaptability and commitment, despite facing increased workloads; (3) implementation strategies, which involve active coordination between villages and local facilitators as well as flexibility in development planning based on the real needs of the community; and (4) the efficiency and effectiveness of the work process, which shows a systematic improvement in infrastructure planning and evaluation despite technical constraints. The final results show an increase in the status of Bulang Village from